Adult Sexual Function Following Hypospadias Repair in Childhood: A Systematic Review and Meta-Analysis of Long-Term Patient Outcomes - Rudini Effendi (22503071) (2025)
Objective To synthesize and quantitatively analyze available evidence regarding sexual function in adults who underwent hypospadias repair during childhood. Methods A systematic review and meta-analysis were conducted based on PRISMA guidelines to assess long-term outcomes of hypospadias repair on adult sexual function. Studies were evaluated for methodological quality, surgical techniques, patient demographics, and primary outcomes related to erectile function, sexual satisfaction, and psychosexual health. Meta-analytic methods were employed to calculate pooled incidences and heterogeneity of key outcomes. Results Thirteen studies were included in the review, with pooled analyses revealing an overall incidence of erectile dysfunction at 12% (95% CI: 7%-19%) and sexual dissatisfaction at 16% (95% CI: 12%-22%). Most studies demonstrated favorable outcomes in erectile function and sexual satisfaction, although variability in outcomes was noted across subgroups. Meta-analysis highlighted significant heterogeneity due to differences in surgical techniques, patient populations, and follow-up durations. Conclusion Hypospadias repair during childhood generally leads to positive long-term sexual function outcomes. However, approximately 12%-16% of individuals may experience persistent challenges. Standardization of outcome measures and long-term follow-up studies are essential to refine surgical approaches and improve patient care. Other Information Published in: Urology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.urology.2025.05.015